Global Financial Crisis and the Nigerian Capital Market - Obayori, Joseph Bidemi; George-Anokwuru Chioma Chidinma B. (Finance & Economics Review, 2020)
Purpose: This paper examined the impact of the global financial crisis on the capital market in Nigeria from 1980-2018. It specifically aimed to determine the impact of the currency crisis and liquidity crisis on the capital market in Nigeria. Methods: The study was time series data based. Data were generated from the Central Bank of Nigeria Statistical Bulletin. The variables were subjected to descriptive statistics and the ’Augmented Dickey-Fuller’ (ADF) unit root test prior to the ’Auto-Regressive Distributed Lag’ (ARDL) model. Results: The outcome of descriptive statistics demonstrated that the parameters were not normally distributed. Also, the ADF unit root test demonstrated that one of the parameters was stationary at I(0) while the remaining two were stationary at I(1). Based on the ARDL results, it was observed that in the short run, the financial crisis has an indirect influence on the performance of Nigerian capital markets. Liquidity crisis, a proxy for the depletion of external reserves has a strong influence on the capital market. The long-run result showed that there is a long-run association amongst the variables. Implications: In view of these findings, the paper recommends that the government should fine-tune its policy mix to ensure that the capital market and the economy do not suffer from the global economic crisis as it takes place.